THE FIRST WORLD WAR HUNDRED YEARS LATER - Turan, Ilter (Turkish Policy Quarterly, 2014)
The Turkish Republic, along with a number of other states in the Balkans, the Caucasus, and the Middle East, represents the end product of the dissolution of multiethnic and multireligious empires. In contrast to other defeated nations of the First World War, it has appeared like Turkey had successfully addressed many of the problems it encountered during the War, or in its immediate aftermath. As time has shown, however, elements of a legacy sometimes disappear and then later reappear; they are defined and redefined, depending on the times, conditions, events, needs, and psychologies. Accordingly, this article explores the direct and indirect effects of the legacy of WWI on Turkey's contemporary developments.